4x-3 supra 7 - 3-x supra 6 = 2x + 1 supra 14 + 13 supra 42
Răspunsuri la întrebare
Răspuns de
4
4x-3/7-3-x/6=2x+1/14+13/42
6(4x-3)-7(3-x)=3(2x+1)+13
24x-18-21+7x=6x+3+13
31x-39=6x+16
31x-6x=16+39
25x=55
x=11/5
x=2,2
6(4x-3)-7(3-x)=3(2x+1)+13
24x-18-21+7x=6x+3+13
31x-39=6x+16
31x-6x=16+39
25x=55
x=11/5
x=2,2
Alex12233:
Multumesc :D
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Chimie,
8 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă
Informatică,
9 ani în urmă